Sonogashira Cross‐Coupling Reaction of Bromocyanofluoro Pyridine Compounds: Access to 5‐ and 6‐Alkynylfluoropyridinamidoximes Scaffolds. Issue 30 (16th August 2021) - Razafindrainibe, Franck; Voros, Camille; Jagadeesh, Yerri; Reddy, Nimmakayala Mallikarjuna; Tissier, Allan; Mardy, Keven; Reihanian‐Hadany, Norbert; Brown, Richard C. D.; Baati, Rachid
Abstract: We disclose a general two‐step procedure to access hitherto unknown and under explored 5‐ and 6‐alkynyl‐3‐fluoro‐2‐pyridinamidoximes from 5‐ and 6‐bromo‐3‐fluoro‐2‐cyanopyridines and a wide range of easily available and bench‐stable terminal alkynes, using Sonogashira cross‐coupling, as the first step. The generation of the polar amidoxime group is realized at a late stage upon treatment of the alkynylfluorocyanopyridine by hydroxylamine. This mild and operationally simple two‐step room temperature process is compatible with enantiopure chiral substrates and various functionality including free alcohols, unprotected and CBz‐protected amines, acetonides, benzyl ethers, amide, imide, di‐substituted alkynes and strained saturated heterocycles. Abstract : A novel and operationally simple two‐step protocol, to access highly valuable and underexplored alkynyl‐fluoro‐pyridinamidoximes compounds is reported. These highly functionalized relevant scaffolds may find numerous applications in heterocyclic and medicinal chemistry.